Trends on Friendly Disability Services: A Bibliometric Review - Dwi Martiningsih (West Science Interdisciplinary Studies, 2023)
Accessing public services and carrying out regular tasks can be difficult for those with disabilities. Disability-friendly services are important to them. This is due to the fact that there are equal rights for all human beings in all aspects of life. To get a structural picture and provide significant insights about disability-friendly services, this study conducted a bibliometric analysis. We used the Scopus database, searching for the keyword "disabled-friendly services*", resulting in a total of 200 documents. VOS-Viewer software is used to visualize documents. The results of the study show that research on disability-friendly services began to appear from 1975 to 2023. A few significant subjects relating to disability-friendly services are examined, along with publication patterns, major areas, prominent papers, and publishing locations. This study also supports the fact that the United States and the United Kingdom originated and conducted the majority of the research on disability-friendly services.  Australia comes in third. At the national level, research on the subject of services for people with disabilities in Indonesia is still scarce (no one has teamed up with researchers from other nations). The findings discussed here provide significant new information and highlight key takeaways for the future development of disability-friendly services. Additionally, the key developments and service areas for people with disabilities are highlighted.